2014
DOI: 10.1155/2014/759436
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Hemospray®in Upper Gastrointestinal Bleeding

Abstract: The high rates of both acute hemostasis and recurrent bleeding suggest that Hemospray may be used in high-risk cases as a temporary measure or a bridge toward more definitive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 18 publications
3
77
1
8
Order By: Relevance
“…Hemospray (Cook Medical, USA), a novel inorganic powder, has recently been approved in Canada for the management of nonvariceal upper digestive bleeding [48,49]. It achieves hemostasis by adhering to the bleeding site, which leads to mechanical tamponade and by promoting thrombus formation [50].…”
Section: Discussionmentioning
confidence: 99%
“…Hemospray (Cook Medical, USA), a novel inorganic powder, has recently been approved in Canada for the management of nonvariceal upper digestive bleeding [48,49]. It achieves hemostasis by adhering to the bleeding site, which leads to mechanical tamponade and by promoting thrombus formation [50].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 66 cases included gastric bleeding (66/234; 28.2%) [Sung et al 2011;Chen et al 2012;Fujita, 2012;Leblanc et al 2013;Smith et al 2013Smith et al , 2014Stanley et al 2013;Yau et al 2014;Sulz et al 2014;Giday et al 2011Giday et al , 2013 and 15 cases of esophageal bleeding (15/234; 6.4%) [Chen et al 2012;Leblanc et al 2013;Yau et al 2014;Smith et al 2014;Sulz et al 2014;Paganelli et al 2014]. A total of 62 cases (62/234; 26.5%) of duodenal bleeding were reported [Sung et al 2011; Leblanc et al 2013;Sargon and Laurie, 2013;Yau et al 2014;Smith et al 2014;Sulz et al 2014;Moosavi et al 2013]. Ibrahim and colleagues studied nine cases of bleeding at the gastroesophageal junction (9/234; 3.85%) [Ibrahim et al 2013].…”
Section: Location Of Bleedingmentioning
confidence: 99%
“…Leblanc and colleagues and Smith and coworkers used hemostatic powder to control bleeding after completion of endoscopic mucosal resection (EMR) [Leblanc et al 2013;Smith et al 2014]. A total of five of the studies reported successfully treated cases of post-polypectomy bleeding from a clipped sessile polyp in the cecum, rectum, transverse and ascending colon, a high-grade tubular adenoma in the rectum, Dieulafoy lesions, and radiation proctitis [Soulellis et al 2013;Yau et al 2014;Smith et al 2014;Holster et al 2014;Sulz et al 2014]. Hemospray efficacy in achieving hemostasis was demonstrated in gastric antral vascular ectasias (GAVE) and in post-sphincterotomy bleeding [Smith et al 2014;Sulz et al 2014;Moosavi et al 2013] Forrest classification Of the 81 bleeding peptic ulcer cases in the human subjects, 38.3% (31/81) were classified as Forrest 1a and 61.7% (50/81) as Forrest 1b.…”
Section: Source Of Bleedingmentioning
confidence: 99%
“…É aplicado sobre as lesões com sangramento ativo, e seu mecanismo de ação é baseado na absorção rápida de água, de modo a formar uma barreira mecânica sobre o ponto de sangramento. 28 Em um projeto piloto coordenado por Sung et al, a eficácia do hemospray foi avaliada em 20 pacientes com sangramento confirmado devido à doença ulcerosa péptica (Forrest Ia e Ib). 95% dos pacientes apresentaram hemostasia inicial, e um paciente possuía pseudoaneurisma, sendo necessária a embolização arterial.…”
Section: Métodos Mecânicosunclassified